Masterpieces of Uzbek Art in Famous Museums of Europe - Turaboyeva Yayra Rustamjonovna (Scientific Trends, 2025)
The article is based on the fact that ancient artworks, telling about the history and culture of the peoples of Uzbekistan, were taken of world for various reasons, and now they have become exhibits of famous museums around the world. In the activities of these museums, historical objects that are considered masterpieces of Uzbek culture testify to folk art, culture, crafts and fine arts and attract the attention of the entire world community.
Keywords: Amirzoda mausoleum, tillagash, Lubeck Museum of Ethnology,Collections of the Naprstek National Museum, isirga, tumor, bosuband, zoomorphic.